Polish affairs. Monthly. . Polish affairs and Problems of Central and Eastern Europe
(1969) - (1973):no.89 titled: Polish affairs and Problems of Central and Eastern Europe; till (1972): Publ. by the Executive Committee of the Polish Council of National Unity with the assistance of the Polish Cultural Foundation.